Perfil de competencias científicas en docentes a través del aprendizaje basado en proyectos (2020)
This research work establishes the relationship between Scientific Competences in teachers and Project-Based Learning (PBL). The main objective is to design a didactic proposal that bases the development of a profile of scientific competences in teachers, through the PBL. The methodology is developed from a Deductive Rationalist epistemological approach, and from a mixed paradigm. The analysis units are made up of elementary school educators in four educational institutions in the city of Barranquilla, selected through a non-probabilistic sampling exercise. For data collection, survey techniques with a Likert-type scale and a documentary analysis of the institutions' PEI were used. Among the main results, it stands out that Projectbased Learning is a relevant active methodology for strengthening scientific competencies in teachers, since it presents a flexible workflow to turn the classroom into a collaborative space for the creation and construction of experiences. memorable educational programs, while meeting the formal demands of the curriculum.